2017
DOI: 10.1111/puar.12769
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Nonprofit Performing Arts Organizations Offer Free Public Access?

Abstract: Evidence for Practice• Key local government officials-such as city managers, mayors, and council members-can influence nonprofit arts organizations' orientation to serving individuals and families with little or no disposable income to spend on arts and culture.• Nonprofit arts organizations deriving a larger share of revenues from market-based sources are less likely to invest in increasing public accessibility.• Nonprofit arts organizations supported by local government and local foundation/corporate donors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 59 publications
(69 reference statements)
1
17
0
1
Order By: Relevance
“…Although our analysis is driven by Weisbrod’s (1998) view that revenue sources can potentially shape the type of benefits conferred by a nonprofit, this study still provides empirical evidence that indirectly corroborates the benefits theory. Our study shows additional support of benefits theory from the nonprofit health sector, adding to the existing empirical support from the human services sector (Fischer et al, 2011; Wilsker & Young, 2010) and the art sector (Kim et al, 2018),…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Although our analysis is driven by Weisbrod’s (1998) view that revenue sources can potentially shape the type of benefits conferred by a nonprofit, this study still provides empirical evidence that indirectly corroborates the benefits theory. Our study shows additional support of benefits theory from the nonprofit health sector, adding to the existing empirical support from the human services sector (Fischer et al, 2011; Wilsker & Young, 2010) and the art sector (Kim et al, 2018),…”
Section: Discussionsupporting
confidence: 69%
“…Their analysis relied on the 2003 core file of more than 289,000 nonprofits collected from the National Center for Charitable Statistics. More recently, Kim, Pandey, and Pandey (2018) examined a data set of 2,823 nonprofit performing arts organizations recorded between 2002 and 2012. They found that free public access to arts programs was positively associated with group benefits–based and public benefits–based resource providers (Kim et al, 2018).…”
Section: Revenue Service and Benefits: Theoretical Perspectivesmentioning
confidence: 99%
“…These questions have been connected to concerns around nonprofit effectiveness and mission drift (Ebrahim et al, 2014). Reliance on earned income can also influence rules of access, for instance, the decision to charge a fee for arts and cultural programs (Kim, Pandey, & Pandey, 2017). Conversely, a nonprofit’s mission can influence the extent to which it uses earned income as a revenue source (Young, Wilsker, & Grinsfelder, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent scholarship that examines the relationship between governments and nonprofits has used stakeholder theory, agency theory, and institutional theory to frame government relationships with nonprofit organizations (Balser & McClusky, 2005;Knox & Gruar, 2007). Although Miragaia, Brito, and Ferreira (2016) suggest that more efficient nonprofits might care more about external stakeholders than about internal ones, studies that are based on stakeholder theory have typically emphasized other key dependent variables at the intersection of government and nonprofit relationships, such as public goal alignment (Kim, Pandey, & Pandey, 2017), ethical dilemmas (Carvalho, Rodrigues, & Branco, 2017), and the balance of institutional logics (Mitchell, Weaver, Agle, Bailey, & Carlson, 2016). Froelich (1999) and Pettijohn et al (2013) suggest that nonprofits are encumbered by federal funding, not for isomorphic reasons, but because the threat of removal of a scarce financial resource means that nonprofits must increase inputs to comply.…”
Section: Resource Dependencementioning
confidence: 99%